Pharmacovigilance analysis of neurological adverse events associated with GLP-1 receptor agonists based on the FDA Adverse Event Reporting System - He Chen; Sixing Liu; Shuai Gao; Hangyu Shi; Yan Yan; Yixing Xu; Jiufei Fang; Weiming Wang; Huan Chen; Zhishun Liu (Scientific Reports)
Abstract We conducted a disproportionality analysis of the FDA Adverse Event Reporting System (FAERS) database (2005 Q2–2024 Q3) to evaluate neurological adverse events (NAEs) associated with six glucagon-like peptide-1 receptor agonists (GLP-1 RAs): exenatide, liraglutide, lixisenatide, dulaglutide, semaglutide, and tirzepatide. Among 28,953 NAE reports associated with GLP-1 RAs, 19 distinct NAE signals were identified using reporting odds ratios (RORs), including dizziness, tremor, dysgeusia, lethargy, taste disorder, presyncope, parosmia, allodynia, and hypoglycemic unconsciousness, etc. Time-to-onset analysis revealed a median latency of 32 days (IQR 7–122) for GLP-1 RA-related NAEs, with 45.28% occurring within 30 days of treatment initiation. Sensitivity analyses using proportional reporting ratios (PRRs), information components (ICs), and empirical Bayes geometric means (EBGMs) confirmed robustness of these signals. While these pharmacovigilance findings underscore the need for heightened clinical vigilance, they represent associations rather than causal relationships, constrained by inherent limitations of FAERS such as reporting bias and confounding. Future prospective studies are needed to confirm these associations and clarify underlying mechanisms.